Integration and conversion of supercritical carbon dioxide coal-fired power cycle and high-efficiency energy storage cycle: Feasibility analysis based on a three-step strategy. (1st October 2022) - Yang, D.L.; Tang, G.H.; Luo, K.H.; Fan, Y.H.; Li, X.L.; Sheng, Q.
Highlights: Integration and conversion of supercritical carbon dioxide coal-fired power cycle and high efficiency energy storage cycle are discussed. A three-step strategy is proposed and various cycles are presented and assessed. First step: the tri-compression coal-fired integrated energy storage cycle has a high efficiency. Second step: the integrated energy storage cycle with various heat sources needs to consider the trade-off of performance criteria. Third step: the high efficiency split expansion adiabatic energy storage cycle is proposed. Abstract: The emission peak/carbon neutrality calls for significantly improved coal-fired power plants. Sustainability of the power plants is critical to meeting the net zero targets in 2050/2060. In this context, it is necessary to investigate the integration and conversion of the supercritical carbon dioxide coal-fired power cycle and the supercritical carbon dioxide energy storage cycle. In this work, the thermodynamic model and performance criteria are firstly presented. After comparison of the two cycles, a three-step strategy for the development of the power cycle is proposed and assessed. First step: when coal still plays an important role as a main energy resource, the integrated tri-compression coal-fired supercritical compressed carbon dioxide energy storage cycle has the highest round-trip efficiency of 56.37%. Second step: with the challenge in utilization of coal energy, a trade-off among the performance criteria must be struck in the integrated cycle with various heat sources. Third step: the adiabatic supercritical compressed carbon dioxide energy storage cycle is proposed, and a high round-trip efficiency of 72.34% is achieved in the split expansion cycle. The present research provides not only a new prospect of the conventional power plants but also design guidance for the supercritical carbon dioxide energy storage cycle.